The effect of short-term training program on sprint speed and vertical jump (comparison study between university soccer players and elite soccer players) - Diyar Muhammed Ali (مجلة علوم الرياضة, 2020)
The aim of this research was to determine the impact of short-term training program on sprint speed and vertical jump between university soccer players and elite soccer players. In this study the participants were of male gender, with an age, height, and weight of 20±2 years, 177.1± 1.5 cm, and 72.6± 2.4 kg, respectively. The initial subjects’ reactions in height and speed prior to the training were measured using t-tests. There were noticeable changes in both of the measured parameters. Furthermore, in the post-training results of the vertical jump were significantly better, with a value of 4 cm improvement, and the (t = 1.443, p ˂ 0.02) which was (8.16%), as for the 20 m sprint in the second test the speed results were increased 0.37 seconds in comparison with the pre-training tests, the (t = 1.088, p ˂ 0.01, or improvement in percentage by (10.95 %). Luebbers et al. (2003) found that the 4-week training program for the vertical jump high increase of 1.9 cm or 2.8%. Kotzamanidis  et al. (2005), used speed training program for 35 of soccer players and found that the t-test revealed significant improvements in the CMJ from pre to post-test (t = 4.201, p ˂ 0.01)